Optimalisasi Pembelajaran Muhadatsah melalui Metode Inside-Outside Circle di Prodi PBA Universitas Islam KH. Ruhiat (UNIK) Cipasung - Taufiq , Furqon; Lita Lestari; Ai Jamliah; Cecep Muttaqin (INDO PUBLISHING, 2025)
Muhadatsah learning, or speaking skills in Arabic, is an important aspect in developing the competencies of students in the Arabic Language Education Study Program (PBA). However, the teaching of this skill still faces challenges, particularly the dominance of traditional teaching methods that provide limited opportunities for active speaking practice. This study aims to optimize Muhadatsah learning through the implementation of the Inside-Outside Circle (IOC) method at the PBA Program of UNIK Cipasung, to examine the impact of this method on students' speaking skills, as well as to identify obstacles and solutions in its implementation. The research method used is classroom action research (CAR) with a qualitative descriptive approach, involving fourth-semester students as subjects. The results show that the IOC method is effective in improving students' speaking skills, demonstrated by an increase in speaking test scores from an average of 65.2 to 80.5 after the method’s application. Additionally, this method creates a more active and interactive learning atmosphere. Challenges encountered, such as difficulties in understanding the rotation mechanism and students' nervousness, can be overcome through clear guidance and ice-breaking sessions. In conclusion, the IOC method is appropriate to be implemented for optimizing Muhadatsah learning and enhancing students' speaking competencies.